Chemical Variations on the p53 Reactivation Theme - Carlos J. A. Ribeiro; Cecília M. P. Rodrigues; Rui Moreira; Maria M. M. Santos (MDPI AG, 2016)
Among the tumor suppressor genes, p53 is one of the most studied. It is widely regarded as the "guardian of the genome", playing a major role in carcinogenesis. In fact, direct inactivation of the TP53 gene occurs in more than 50% of malignancies, and in tumors that retain wild-type p53 status, its function is usually inactivated by overexpression of negative regulators (e.g., MDM2 and MDMX). Hence, restoring p53 function in cancer cells represents a valuable anticancer approach. In this review, we will present an updated overview of the most relevant small molecules developed to restore p53 function in cancer cells through inhibition of the p53-MDMs interaction, or direct targeting of wild-type p53 or mutated p53. In addition, optimization approaches used for the development of small molecules that have entered clinical trials will be presented.